Discovery of a variable energy-dependent X-ray polarization in the accreting neutron star GX 5-1 - Fabiani, Sergio; Capitanio, Fiamma; Iaria, Rosario; Poutanen, Juri; Negro, Michela; et al. (My University, 2023)
We report on the coordinated observations of the neutron star low-mass X-ray binary (NS-LMXB) \gx in X-rays (IXPE, NICER, Nustar and INTEGRAL), optical (REM and LCO), near-infrared (REM), mid-infrared (VLT VISIR), and radio (ATCA). This Z-source was observed by \IXPE twice in March-April 2023 (Obs. 1 and 2). In the radio band, the source was detected, but only upper-limits to the linear polarization were obtained at a 3σ level of 6.1% at 5.5 GHz and 5.9% at 9 GHz in Obs.~1 and 12.5% at 5.5~GHz and 20% at 9~GHz in Obs.~2. The mid-IR, near-IR and optical observations suggest the presence of a compact jet which peaks in the mid- or far-IR. The X-ray polarization degree was found to be 3.7%±0.4% (at 90% confidence level) during Obs.~1 when the source was in the horizontal branch of the Z-track and 1.8%±0.4% during Obs.~2 when the source was in the normal-flaring branch. These results confirm the variation of polarization degree as a function of the position of the source in the color-color diagram as for previously observed Z-track sources (Cyg~X-2 and XTE~1701−462). Evidence for a variation of the polarization angle ∼20° with energy is found in both observations, likely related to the different, non-orthogonal polarization angles of the disk and Comptonization components which peak at different energies.
Authors: - Sergio Fabiani, Fiamma Capitanio, Rosario Iaria, Juri Poutanen, Andrea Gnarini, Francesco Ursini, Ruben Farinelli, Anna Bobrikova, James F. Steiner, Jiri Svoboda, Alessio Anitra, Maria C. Baglio, Francesco Carotenuto, Melania Del Santo, Carlo Ferrigno, Fraser Lewis, David M. Russell, Thomas D. Russell, Jakob van den Eijnden, Massimo Cocchi, Alessandro Di Marco, Fabio La Monaca, Kuan Liu, John Rankin, Martin C. Weisskopf, Fei Xie, Stefano Bianchi, Luciano Burderi, Tiziana Di Salvo, Elise Egron, Giulia Illiano, Philip Kaaret, Giorgio Matt, Romana Mikušincová, Fabio Muleri, Alessandro Papitto, Iván Agudo, Lucio A. Antonelli, Matteo Bachetti, Luca Baldini, Wayne H. Baumgartner, Ronaldo Bellazzini, Stephen D. Bongiorno, Raffaella Bonino, Alessandro Brez, Niccolò Bucciantini, Simone Castellano, Elisabetta Cavazzuti, Chien-Ting Chen, Stefano Ciprini, Enrico Costa, Alessandra De Rosa, Ettore Del Monte, Laura Di Gesu, Niccolò Di Lalla, Immacolata Donnarumma, Victor Doroshenko, Michal Dovčiak, Steven R. Ehlert, Teruaki Enoto, Yuri Evangelista, Riccardo Ferrazzoli, Javier A. Garcia, Shuichi Gunji, Kiyoshi Hayashida, Jeremy Heyl, Wataru Iwakiri, Svetlana G. Jorstad, Vladimir Karas, Fabian Kislat, Takao Kitaguchi, Jeffery J. Kolodziejczak, Henric Krawczynski, Luca Latronico, Ioannis Liodakis, Simone Maldera, Alberto Manfreda, Frédéric Marin, Andrea Marinucci, Alan P. Marscher, Herman L. Marshall, Francesco Massaro, Ikuyuki Mitsuishi, Tsunefumi Mizuno, Michela Negro, Chi-Yung Ng, Stephen L. O’Dell, Nicola Omodei, Chiara Oppedisano, George G. Pavlov, Abel L. Peirson, Matteo Perri, Melissa Pesce-Rollins, Pierre-Olivier Petrucci, Maura Pilia, Andrea Possenti, Simonetta Puccetti, Brian D. Ramsey, Ajay Ratheesh, Oliver J. Roberts, Roger W. Romani, Carmelo Sgrò, Patrick Slane, Paolo Soffitta, Gloria Spandre, Douglas A. Swartz, Toru Tamagawa, Fabrizio Tavecchio, Roberto Taverna, Yuzuru Tawara, Allyn F. Tennant, Nicholas E. Thomas, Francesco Tombesi, Alessio Trois, Sergey S. Tsygankov, Roberto Turolla, Jacco Vink, Kinwah Wu, and Silvia Zane